Balloon-occluded retrograde transvenous obliteration with lauromacrogol sclerosant foam for gastric varices - Zhiyang Wu; Wei Wu; Cheng Tao; Qin Liu; Wenchang Li; Qinbing Wang; Wei Huang; Junwei Gu; Xiaoyan Fei; Zhongmin Wang; Xiaoyi Ding (Journal of Interventional Medicine, 2022)
Objectives: To evaluate the safety and efficacy of balloon-occluded retrograde transvenous obliteration (BRTO) using lauromacrogol sclerosant foam for gastric varices (GVs) with gastrorenal venous shunts. Methods: Data of GV patients treated with BRTO using lauromacrogol sclerosant foam in 2016–2020 were retrospectively analyzed along with procedural success rate, complications, and follow-up efficacy. Results: A total of 31 patients were treated with BRTO. The sclerosant foam was prepared by mixing iodinated oil, lauromacrogol, and air at a 1:2:3 ratio. The BRTO procedure was successfully completed in 93.5% of patients. One patient was allergic to the lauromacrogol injection. A mild postoperative fever occurred in three patients. One patient experienced grand mal seizures after the procedure. There was no significant difference in the median Child-Turcotte-Pugh scores before versus after BRTO. Complete GV resolution was observed in 93.1% of patients. One patient underwent endoscopic treatment for the development of high-risk esophageal varices. Another patient underwent transjugular intrahepatic portosystemic shunt placement for the aggravation of ascites. Conclusions: Lauromacrogol sclerosant foam is safe and effective in patients undergoing BRTO for GV.